Enhanced kernel set promoted by synchronous pollination determines a tradeoff between kernel number and kernel weight in temperate maize hybrids - Uribelarrea, Martin (2008)
Maize (Zea mays L.) grain yield is strongly related to the number of harvested kernels, where kernel number can be increased by synchronously pollinating silks rather than allowing them to be progressively pollinated as they naturally appear from the husks. However, there is scarce evidence on how this practice affects kernel weight (KW) and plant grain yield (PGY), and no report exists on its effects when combined with treatments aimed to reduce apical dominance, like male sterility and detasseling. Field experiments were conducted in two growing seasons (Exp1 and Exp2) using two hybrids, cropped at contrasting stand densities (3 and 9 plants per m2) and including (i) male-fertile and male-sterile versions, (ii) tasseled and detasseled plants, and (iii) natural (NP) and synchronous pollination (SP; pollen added manually to ears bagged 5 days after initial silking) systems. Tassel growth of sterile and fertile versions was also evaluated in a separate experiment (Exp3). Detasseling increased the number of ears per plant reaching silking (P < 0.001) of NP plants, but this beneficial effect of reduced apical dominance did not improve kernel number per plant (KNP) or PGY. Similarly, the early arrest of anther growth in male-sterile plants had no clear benefit on KNP. In contrast, KNP was enhanced by synchronous pollination (range between -13% and +71%; average of +15.4% in Exp1 and +3.9% in Exp2). However, this pollination system promoted a decreased in KW (range between -30% and +4%; average of -11.8% in Exp1 and -7.8 in Exp2) such that the treatment had no effect on PGY (range between -19% and +37%; average of +1% in Exp1 and -4% in Exp2). Because plant growth rate around flowering was not different between pollination treatments, assimilate availability per kernel was reduced from ovary fertilization onwards in synchronously pollinated plants when compared to open pollinated plants. This explains the reduced KW when increasing KNP by synchronous pollination. In summary, none of the imposed treatments allowed grain yield to be increased at the plant level.